Adjacency criticality: a simple yet effective metric for statistical timing yield optimisation of digital integrated circuits. Issue 7 (22nd October 2019) - Ebrahimipour, Seyed Milad; Ghavami, Behnam; Raji, Mohsen
Abstract : As CMOS devices become smaller, process variations‐induced uncertainty imposes a large spread in the circuit timing and therefore, it becomes one of the main issues for circuit yield. To analyse/optimise the timing of the circuit under process variation effects, statistical analysis/optimisation techniques are more suitable than the traditional static analysis/optimisation counterparts. Statistical gate sizing is an effective technique that is widely used to guide the timing yield improvement of digital circuits. Gate criticality, defined as the probability that a gate lies on a critical path, forms the basis for many of the existing statistical gate sizing techniques. Here, the authors introduce adjacency criticality to address the drawbacks of the conventional definition of gate criticality. It is defined as the probability of manufacturing a chip in which the gate lies on the critical path due to process variation considering the effect of the gates in its fan‐out cone. Furthermore, the authors present the levelised Adjacency Criticality metric which provides a trade‐off between the runtime of the criticality metric and accuracy of the Adjacency Criticality metric. In order to show the efficacy of the proposed metric, an adjacency criticality‐based statistical gate sizing method is presented for improving timing yield of the circuit.